Multiple sclerosis and optic nerve: an analysis of retinal nerve fiber layer thickness and color Doppler imaging parameters - Akçam, H T (Nature Publishing Group, 2014)
PURPOSE: To compare both retinal nerve fiber layer thickness and orbital color Doppler ultrasonography parameters in patients with multiple sclerosis (MS) versus healthy controls. METHODS: This is an observational case–control study. Forty eyes from MS patients and twenty eyes from healthy volunteers were examined. Eyes were classified into three groups as group 1, eyes from MS patients with previous optic neuritis (n=20); group 2, eyes from MS patients without previous optic neuritis (n=20); and group 3, eyes from healthy controls (n=20). Following complete ophthalmologic examination and retinal nerve fiber layer thickness measurement for each group, blood flow velocities of posterior ciliary arteries, central retinal artery, ophthalmic artery, and superior ophthalmic vein were measured. Pourcelot index (resistive index), an indicator of peripheral vascular resistance, was also calculated. The statistical assessment was performed with the assistance of Pearson's Chi-square test, Mann–Whitney U-test, Kruskal–Wallis test, and Spearman's correlation test. RESULTS: The studied eyes exposed similar values in terms of intraocular pressure and central corneal thickness, implying no evidence in favor of glaucoma. All nerve fiber layer thickness values, except superior nasal quadrants, in group 1 were found to be significantly thinner than groups 2 and 3. Blood flow velocity and mean resistivity index parameters were similar in all the groups. CONCLUSIONS: In MS patients, especially with previous optic neuritis, diminished retinal nerve fiber layer thickness was observed. Contrary to several studies in the current literature, no evidence supporting potential vascular origin of ocular involvement in MS was found.